(untitled) (Research, Society and Development, 2020)
Aim: to determine the sociodemographic characteristics, clinica, functional and depressive symptoms related to the frailty burden in community-dwelling older adults with T2DM. Methods: observational, analytical cross-sectional study with diabetic older adults, aged ≥ 60 years, who are ambulatory and non-amputated. Sociodemographic characteristics, clinical-functional, and depressive symptoms and frailty phenotype were evaluated. A stepwise multivariate logistic regression analysis (p<0,05 and 95% Confidence Interval) was conducted. Results: The sample consisted of 125 participants (63,2% women) with a mean age of 68,7 ± 6,5 years. Nearly half the participants met the criteria for the lowest frailty load group, and the low physical activity level was most prevalent (72,0%). The final regression model showed that frailty burden was significantly associated with age (p=0,016; [1,316-8,794]), education (p=0,002; [1,680-10,623]), lower limb pain (p<0,001; [1,935-11,766]) and TUGT (p=0,031; [1,145-15,659]). This model presented 80.9% accuracy. Conclusions: Older adult patients with T2DM who present high frailty burden are in the age group of 70 years or more, use 5 or more medications, have had T2DM diagnosis for 6 years or more, have altered glycated hemoglobin and fasting glycemia, have longer walking and show higher depressive symptoms. Older people with lower frailty load have higher education and income.